2019
DOI: 10.1186/s40691-019-0185-1
|View full text |Cite
|
Sign up to set email alerts
|

Consumer attitudes toward downward extensions: an exploration of Giordano’s extension in Hong Kong

Abstract: Given that numerous fashion brands constantly struggle to survive, it is important to learn how consumers evaluate and change their attitudes toward the downward extensions of mass-production fashion businesses, particularly those that originate in Hong Kong. Through capitalizing on the parent brand’s equity earned through enhancing consumer preferences and building loyalty, companies’ brand extension strategies can lead to better profits and sales for fashion brands. Based on the categorization theory and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 89 publications
0
8
0
Order By: Relevance
“…The transfer of affective commitment to a parent company to the intention to attend the related sports games and purchase licensed merchandise of the sports franchise is consistent with the concept of brand extension (e.g., FuBon and ChinaTrust have leveraged financial service profits into a new product categoryprofessional baseball franchises) [54]. Moreover, trust in and familiarity with a parent brand exerts a positive influence on consumers' evaluations of product transferability and purchase intention [55].…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The transfer of affective commitment to a parent company to the intention to attend the related sports games and purchase licensed merchandise of the sports franchise is consistent with the concept of brand extension (e.g., FuBon and ChinaTrust have leveraged financial service profits into a new product categoryprofessional baseball franchises) [54]. Moreover, trust in and familiarity with a parent brand exerts a positive influence on consumers' evaluations of product transferability and purchase intention [55].…”
Section: Discussionmentioning
confidence: 56%
“…These findings imply that more affectively attached consumers exhibit greater purchase intention for brand extension products. Moreover, trust in a parent brand and familiarity with the brand are factors that positively influence consumers' evaluations of brand extension, and product transferability positively influences purchase intention [55]. Based on the aforementioned review of brand extension literature, we hypothesized that spectators' affection toward a parent company transfers to the intention to purchase brand extension products; relevant here are purchases with respect to a professional sports franchise, including game attendance and merchandise purchase.…”
Section: Transferability From Affective Commitment To a Parent Company To The Intention Of Purchasing Licensed Merchandise And Attending mentioning
confidence: 99%
“…The same trust mechanisms exist for intimate relationships in virtual contexts. For example, in a book recommendation system, individuals tend to adopt recommendations that are more similar to their values and beliefs (Ziegler and Golbeck, 2007 ; Zeng et al, 2019 ). When people gather in the same short video application platform, they tend to view others on that platform in a positive way, which apparently enhances their trust (McKnight et al, 1998 ; Casalo et al, 2013 ).…”
Section: Theoretical Foundation and Hypothesis Developmentmentioning
confidence: 99%
“…For instance, Maotai wine, which is perceived as a symbol of power and luxury in China, launched Maotai Prince wine that is aimed at the middle market; Parker pen, dubbed the “king of the pens,” sells its mass-market pens for under $3 each. It is suggested that downward line extension leads to the popularization or democratization of luxury goods (Shirai, 2022), covers broader consumer segments (Goetz et al , 2014), meets high market demand for cost-effective products (Shirai, 2022) and affects consumers’ purchase intentions (Zeng et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…As schema theory provides a theoretical basis for extension evaluation (Allman et al , 2016; Su and Kunkel, 2019), this study explores the relationship between these two types of products and consumers’ purchase intentions by introducing perceived fit as a potential mediator. It has been demonstrated that perceived fit is positively correlated with extension evaluation and consumers’ purchase intentions (Choi et al , 2010; Hill and Lee, 2015; Zeng et al , 2019; Zheng et al , 2019). Moreover, self-congruity, which refers to the consistency between an individual’s self-image and a brand’s image, plays a crucial role in brand evaluation (Li et al , 2022; Rabbanee et al , 2020).…”
Section: Introductionmentioning
confidence: 99%